The promise of the Grand Canyon : John Wesley Powell's perilous journey and his vision for the American West - Ross, John F., 1958- (New York, New York : Viking, 2018)
Using new research, a second-hand recreation of Powell's expedition through the Grand Canyon reveals how his experiences influenced his second career as a scientist, bureaucrat, and land-management pioneer.
Includes bibliographical references (pages 343-365) and index.
Keywords: Powell, John Wesley, -- 1834-1902; Powell, John Wesley, -- 1834-1902; Colorado River (Colo.-Mexico) -- Description and travel; Grand Canyon (Ariz.) -- Description and travel; Southwest, New -- Discovery and exploration; Colorado River (Colo.-Mexico) -- Description and travel; Grand Canyon (Ariz.) -- Description and travel; New Southwest -- Exploring expoditions